Effect of cognitive remediation therapy in anorexia nervosa: a systematic review and meta-analysis - Alserihi, Anas R.; Hubayni, Wejdan A.; Alotaibi, Solaf Hilal; Bahkali, Sadeem; Alqurashi, Shatha; Abualola, Muhannad Sadakah; Alsaleh, Ahmad Mohammed (Frontiers in Psychiatry, 2024)
Anorexia nervosa (AN) can significantly affect cognitive well-being. Cognitive remediation therapy (CRT) is regarded as one of the effective treatments for cognitive impairment in some mental illnesses such as schizophrenia, bipolar disorder, and attention deficit. For this reason, this systematic review and meta-analysis aim to assess the effectiveness of CRT in patients with AN.We conducted a search of Medline, ClinicalTrials.gov, and the Cochrane Database of Systematic Reviews from the inception of each database through April 8, 2023. Randomized clinical trials evaluating the effectiveness of CRT in comparison to placebo or other psychological treatments in patients with AN were included. The quality of the studies was assessed using the revised Cochrane risk-of-bias tool. For meta-analysis, effect sizes were measured using mean difference (MD) utilizing the random-effects model and inverse variance (IV) technique. To evaluate the certainty of the evidence, we applied the Grading of Recommendations Assessment, Development, and Evaluation (GRADE) criteria. The study was registered in PROSPERO, ID: CRD42023411784.In the systematic review, six studies were included, of which four underwent meta-analysis. Among these, three trials encompassing 413 participants showed that CRT was associated with improved cognitive flexibility compared to control at the end of treatment (MD = -0.21, 95% CI [-0.44, 0.02], P=0.81, I 2 = 0%). In two trials with 143 patients, those who received CRT showed similar effects on the severity of AN symptoms compared to the control group in the self-reporting questionnaires: EDE-Q (MD = -0.25, 95% CI [-0.76, 0.27], P=0.77, I 2 = 0%) and EDEQOL (MD = -0.19, 95% CI [-0.41, 0.03], P=0.84, I 2 = 0%).CRT did not show a statistically significant difference compared to the control group in improving abstract thinking skills and quality of life in individuals with AN. That indicates that CRT's efficacy remains inconclusive. Further research with larger, more diverse samples is needed to determine its long-term effects and potential benefits.